(untitled) (Bangladesh Journal of Animal Science, 2016)
This experiment was conducted to evaluate the quality of existing ultra-high temperature (UHT) treated milk available in two selected town markets of Bangladesh. A total of 27 UHT milk samples from three different brandsPran Dairy (A), Aarong Dairy (B) and Farm Fresh (C) were collected from local markets at Mymensingh and Gazipur districts during the period of 1stSeptember to 29th November, 2014. Parameters studied in this experiment were organoleptic (flavour, consistency, colour and appearance), physic-chemical (specific gravity, acidity, total solids, solids-not-fat, fat, protein, lactose, and ash) and microbiological (Total Viable Count and Coliform Count). All the samples were similar in respect of color, flavor, taste and texture, and no significant difference was observed. However, significant differences were revealed (p<0.05) in case of specific gravity, acidity, total solids, solids-not-fat, and protein content. On the other hand, insignificant differences were found (p>0.05) in case of fat, lactose, and ash content. Total Viable Count and Coliform count were found to be nil in all the milk samples. Milk samples of Farm Fresh UHT milk were superior to other brands of UHT Milk in terms of contents of total solids (119.23±0.57 g/kg),fat (34.97±0.35g/kg), lactose (43.23±0.51g/kg), and ash (7.00±0.26g/kg). Though there were some fluctuations in all the parameters studied, all the milk samples conformed to the standard values for UHT milk, and in general all of the UHT milk samples studied in this experiment was of good quality. Bang. J. Anim. Sci. 2015. 44 (3):132-136